ANALISA DISPERSI MATERIAL SERAT KISI BRAGG MENGGUNAKAN METODE SOFTWARE OPTIGRATING - Elisa Saadah; Saktioto '; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The analysis of material dispersion on Fiber Bragg Grating (FBG) by using silica material for the core and cladding with germania-doped silica material has been determined. FBG is used for multi mode. Parameters that fluctuate in this study is the grating length of FBG while the value of the period, the modulation index and the amount of grating is keptconstant.   The method used is OptiGrating software, which is a software evaluating a transfer matrix to analyze the grating on the FBG. The results showed the higher value of long-grating given in FBG, the lower valley formed transmission coefficients. The pattern of the transmission coefficients of FBG found the difference between FBG dispersed material and no dispersed material. The dispersed material produced some FBGtransmission coefficients with a certain value where the bigger one has the pattern point value the lower the transmission coefficients is produced. The FBG with no  material dispersion results the constant of the transmission coefficients.